THE NEW ASIA-AFRICA STRATEGIC PARTNERSHIP (NAASP): AN INFORMAL INTERGOVERNMENTAL ORGANISATION (IIGO) TO ADDRESS WILDLIFE TRAFFICKING AND BIOPRINTING - Marina Abdul Majid (Journal of Islamic, Social, Economics and Development, 2019)
Although the New Asia-Africa Strategic Partnership (NAASP), an Informal Intergovernmental Organisation (IIGO), can address wildlife trafficking, this potential has remained unnoticed. Artificial rhino horns, ivory, and pangolin scales may become available in the future through bioprinting, which could complicate related law enforcement in Africa and Southeast Asia in terms of distinguishing genuine parts. Hence, the present study aims to explore whether the NAASP can be utilised to discuss wildlife trafficking problems among African and Southeast Asian countries and to deliberate on bioprinting as a technological solution. Thailand, through its 2015 declaration in the Asia-Africa Parliamentary Conference, emphasised that wildlife trafficking should be included within NAASP’s scope. The transfer of technology mentioned in two declarations of the NAASP allows bioprinting to be discussed as well. The present study contributes to the sparse literature on wildlife trafficking and bioprinting elaborated in the context of the NAASP and the Asian-African Legal Consultative Organisation (AALCO), which have barely been explored by the existing literature.